EFEK KONSUMSI BISKUIT UBI UNGU TERHADAP SALIVA DALAM UPAYA PENCEGAHAN KARIES - Marlindayanti Marlindayanti (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2019)
The occurrence of caries is due to an unbalanced demineralization and remineralization process. Both of theseprocesses are affected by the salivary acidity (pH). Eating foods containing complex carbohydrates (phosphorusand calcium) is very influential in the remineralization process. One type of food containing phosphorus andcalcium is purple sweet potato biskuits. Wheat-based biskuits are used as a comparison. The purpose of thisstudy was to determine the average salivary pH, time (minutes) needed for remineralization or restore normalpH. The population of this study was children aged 10-12 years at SDN 35 Palembang. A sample of 20respondents were divided into 2 groups, namely the group that consumed purple yam biskuits and the group thatconsumed wheat biskuits. The research design is a quasi-experimental study. From the results of the study it wasfound that the average amount of saliva pH after consumption of purple yam biskuits was 8.58 and the averagepH of saliva after consumption of wheat biskuits was 6.45. The normal salivary pH return time after consumingpurple yam biskuits is 30 minutes (average salivary pH 7.39), and after consuming wheat biskuits it is 40minutes (mean salivary pH 7.18). It can be concluded that purple sweet potato biskuits have the advantage ofslowing down the demineralization process after consuming carbohydrates and accelerating theremineralization process.